Влияние ионно-плазменной обработки на физико-химические свойства и биосовместимость поверхности материалов на основе полилактида - Лапуть, Сергей Владимирович; Кудряшов, Сергей Владимирович; Ахмадеев, Юрий Халяфович; Курзина, Ирина Александровна (Перспективы развития фундаментальных наук. Т. 2 : сборник научных трудов XIX Международной конференции студентов, аспирантов и молодых ученых, 26-29 апреля 2022 г.)
The effect of a nitrogen barrier and arc low-temperature plasma on the surface physicochemical properties and biocompatibility of the polylactide based scaffolds is investigated. The chemical composition of the modified scaffolds surface has been researched by X-ray photoelectron spectroscopy. The viability of cells on modified surface of polylactide based scaffolds was assessed after cultivation.